TANGGUNG GUGAT PIHAK YANG MENGGANDAKAN DAN MEMPUBLIKASI LAGU “AKAD” TANPA IZIN PENCIPTA - Yolanda Halim; Yoan Nursari Simanjuntak; Irta Windra Syahrial (Perpustakaan Universitas Surabaya, 2023)
Abstract— Songs or music are forms of creation that are protected by Law Number 28 of 2014 concerning Copyright. Songs or music are works in the field of art that can be enjoyed by the general public through various media, one of which is YouTube and song-streaming activities. Songs or music are produced by creators based on inspiration, thoughts, abilities, imagination, and skills or expertise which are then realized in a real or concrete form and are original. A songwriter or music has a copyright, copyright is an exclusive right that arises automatically when the creation is realized in a real or concrete form. Song or music copyright consists of moral rights and economic rights and is a form of protection and appreciation for the creators of songs or music. However, irresponsible parties often violate the copyright of a songwriter or music, resulting in the creator experiencing losses. Like the song